Effect of the Using of Racing Exhaust with variation Soundproofing Material Against Exhaust Emissions and Noise on 4 Stroke Motorcycle - M Nasir; Hannyka Febriano; Balisranislam Balisranislam (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2021)
This study discusses the effect of using a racing exhaust with asbestos and stainless steel-based filters. The purpose of this study is to find out how big the role of racing exhaust filters in reducing noise and exhaust emissions. This study uses an experimental method with the static comparison design. The object of this research is Honda Beat injection motorcycle 2017. The data from this study were taken from testing standard exhaust, stainless steel, and asbestos. Based on the research that has been done, it can be concluded that the use of stainless steel-based filters is effective in reducing HC emissions compared to standard exhausts and racing exhausts with asbestos filters, stainless steel filters are also effective in reducing noise by 4.4% compared to exhausts with asbestos filters. Penelitian ini membahas tentang pengaruh dari pemakaian knalpot racing dengan saringan berbahan dasar asbes dan stainless steel. Tujuan dari penelitian ini yaitu mengetahui seberapa besar peranan saringan knalpot racing dalam mereduksi kebisingan dan emisi gas buang yang dihasilkan. Penelitian ini menggunakan metode eksperimen dengan desain the static comparison design. Objek dari penelitian ini adalah sepeda motor Honda Beat injeksi tahun 2017. Data dari penelitian ini diambil dari pengujian knalpot standar, stainless steel, dan asbes. Berdasarkan hasil penelitian disimpulkan bahwa penggunaan saringan berbahan dasar stainless steel efektif mereduksi emisi HC dibanding knalpot standar dan knalpot racing dengan saringan asbes, saringan stainless steel juga efektif mereduksi kebisingan sebesar 4,4% dibandingkan kanlpot dengan saringan asbes.